KEBIJAKAN PEMERINTAH DAERAH DALAM PELAKSANAAN PENDIDIKAN DI KABUPATEN KONAWE - Hartono Hasim (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Context of the implementation of education in Konawe there are many problems arise. Understanding and strong commitment from the local government is very necessary in order to answer the existing constraint. This can be seen in the formulation of legislation. As expressed in Article 2 of Law No. 20 of 2003 that: "The national education based on Pancasila and the Constitution of the Republic of Indonesia Year 1945. Implementation Konawe education is a process of implementation starting from: 1) Planning Education 2) Organizing Education; 3) Direction Education Activity; 4) Implementation of Education; 5) Monitoring of Education (Monitoring and Evaluation).